Pengukuran Indeks Kepuasan Masyarakat Terhadap Pelayanan Dan Kualitas Data Penginderaan Jauh - Hedy Izmaya; Dety Purnamasari (Jurnal Informatika: Jurnal Pengembangan IT, 2021)
Technology and Data Center (Pustekdata) LAPAN in 2016 has distributed remote sensing satellite data of 86,176 scenes to 323 government institutions. In 2016, the data service has also achieved the quality management standard ISO 9001: 2015 and the value of the Community Satisfaction Index (IKM) which reached 82 with a very satisfactory predicate. To maintain and improve performance in data services to users, it is necessary to study the needs of users for the required remote sensing data, namely by conducting a survey to users of remote sensing data, especially High Resolution Satellite Imagery (CSRT). Eight indicators are used to measure community satisfaction from the 14 indicators of the Community Satisfaction Index in accordance with the Decree of the Minister of State Apparatus Empowerment Number: KEP/25/M.PAN/2/2004 concerning Guidelines for the Preparation of IKM Service Units of Government Agencies including BUMN/BUMD. The population in this study is all data buyers from 2017, 2018 and 2019. The survey data are then reviewed and analyzed using statistical analysis with instrument refinement by statistically validating the survey data. The 2017 Community Satisfaction Index scored 90.69% with the predicate "Very Good". In 2018 there was an increase of 18.41% with a value of 93.69% obtaining the "Very Good" predicate. In 2019, with a total of 516 respondents, an increase of 3.12% was obtained, a score of 96.81% was obtained with the predicate "Very Good".